Influence of hemolysis on routine clinical chemistry testing - Haque, Mahmudul; Nahar, Nazibun; Sultan, Md Tipu; Aziz, Rehana; Islam, Sirajul; Mazed, MA (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v18i1.3814 Journal of Chittagong Medical College Teachers' Association 2007: 18(1):12-14